A RESEARCH ON THE DIFFERENCES BETWEEN LEADERSHIP STYLES AT THE HIERARCHICAL LEVELS OF EDUCATIONAL INSTITUTIONS (Third Sector Social Economic Review, 2020)
Purpose of this study is to determine how lower, middle and upper-level managers perceive superior leadership behaviors in educational institutions and whether their perception of leadership behavior differs according to hierarchical levels. While measuring leadership behaviors, we did not ask managers to evaluate their behavior; but we tried to determine how the employees perceive the behaviors of their closest superior. We have determined our working universe as upper, middle and lower-level managers working at Akhmet Yassawi University. The research data were collected from 101 managers with the survey technique. Managers were asked questions about vision determination, environmental sensitivity, exhibiting extraordinary behaviors, taking personal risks, showing sensitivity to member needs and maintaining the status quo, and analyzes were made based on the responses given by the senior, middle and lower management levels. To measure the leadership behavior of managers, Leadership Behavior Measurement Survey and Leadership Effectiveness Analysis were used.
Keywords: Leader; Leadership; Leadership Styles; Leadership Behaviors; Leadership Approaches; Manager; Hierarchical Levels